RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF KOMPUTER DAN JARINGAN DASAR DI SMK - Rahmat Rahmat; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study was discussed about the design of interactive learning media on Computer and Basic Network subject at the first year students. The purpose of this study was developed a valid and practical interactive learning media by using Adobe Director Software on Computer and Basic Network subject at SMKS Mahyal Ulum Al-Aziziyah. This type of study used the IDI model (Instructional Development Institute). The step of this study consists of three steps, namely (1) define, (2) develop, and (3) evaluate. To collect the data, some instruments are used to analyze such as validation questionnaire, and practical questionnaire. The data analysis were used the Aiken's V formula. Based on the results of the study, it can be concluded that the design was produced interactive learning multimedia products by using Adobe Director Software in Computer and Basic Network subjects at the class X TKJ of SMKS Mahyal Ulum Al-Aziziyah. It could be seen based on the Aiken's V coefficient value of 0.78 which is declared valid and practical with an average value of 83.72% after going through the development step which are analyzed based on validity and practicality. Keywords: Interactive Learning Media, Adobe Director, Instructional Development Institute, Aiken’s V.